CCNP BCMSN portable command guide - Empson, Scott (Self-study guide., 2007)
All the BCMSN 642-812 commands in one compact, portable resource Preparing for the CCNP® certification? Working as a network professional? Here are all the CCNP-level commands for the BCMSN exam you need in one condensed, portable resource. The CCNP BCMSN Portable Command Guide is filled with valuable, easy-to-access information and is portable enough for use whether you're in the server room or the equipment closet. This book will help you memorize commands and concepts as you work to pass the CCNP BCMSN exam (642-812). The guide summarizes all CCNP certification-level Cisco IOS® Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real-world scenarios. Sample configurations throughout the book provide you with a better understanding of how these commands are used in simple network designs. The topics in this portable command guide cover how to do the following: Implement VLANs Conduct the operation of Spanning Tree Protocol and EtherChannel in a hierarchical network Implement inter-VLAN routing Implement gateway redundancy technologies Describe and configure wireless client access Describe and configure security features in a switched network Configure support for voice Scott Empson is currently the assistant program chair of the bachelor of applied information systems technology degree program at the Northern Alberta Institute of Technology in Edmonton, Alberta, Canada, teaching Cisco® routing, switching, and network design courses in certificate, diploma, and applied degree programs at the post-secondary level. He is also the program coordinator of the Cisco Networking Academy® Program at NAIT, a Regional Academy covering central and northern Alberta. He has earned three undergraduate degrees and currently holds several industry certifications, including CCNP, CCDA®, CCAI, and Network+. Access all CCNP BCMSN commands--use as a quick offline resource for research and solutions Logical "how-to" topic groupings provide one-stop research Great for review before taking the CCNP BCMSN certification exam Compact size makes it easy to carry with you, wherever you go "Create your own journal" section with blank, lined pages allows you to personalize the book for your needs This book is part of the Cisco Press® Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco® certification exams. Titles in the Cisco Press Certific ...